Relationship between Angiotensin Converting Enzyme (ACE) and Cellulite - Annisa Astari; Putra, Imam Budi; Jusuf, Nelva Karmila (Journal of Society Medicine, 2024)
Introduction: Cellulite is a local metabolic disorder in subcutaneous tissue characterized by changes in skin topography, occurring in parts of the body with a large accumulation of fat tissue, especially thighs, buttocks, hips, and abdomen. Angiotensin converting enzyme is a zinc metallopeptidase, distributed on the surface of endothelial cells. Increased ACE levels cause microcirculation disorders, adipocyte hypertrophy, increased extracellular matrix, and stimulate the emergence of inflammatory cytokines which will cause an increase in the inflammatory response in the tissue, stimulate fibrogenic response and influences the appearance of cellulite. The aim of this study was too determine the relationship between ACE and cellulite. Method: This study was an observational study with a cross-sectional design of 40 cellulite patients and 40 controls. Each patient underwent history, dermatological examination, and blood sampling to assess ACE levels by ELISA test. These data were analyzed statistically using the Chi square test. Results: The mean ACE level in cellulite was 66.78±15.38 µg/ml. The highest age with cellulite was 26–35 years 17 subjects (42.5%). Most of them had a family history of cellulite from their mother 22 subjects (55%). The majority of cellulite are located on the femoral and gluteus regions by 27 subjects (67.5%). The result of this study showed that there was a relationship between high ACE levels causing a risk of 4.5 times for cellulite (p = 0.002). Conclusion: There is a relationship between ACE levels and cellulite.